Relative Warp Analysis of the Forewings of Male Dragonfly Neurothemis ramburii (Journal of Informatics and Mathematical Sciences, 2017)
This study was conducted to determine variations in the forewings of N. ramburii collected from 3 selected rice agroecosytem in Lanao del Norte. Since the quantitative description, analysis and interpretation of shape variation in biology have become a fundamental area of research; the geometric method of morphometrics was used in this study aimed at assessing its variations. For the methodology, anatomical landmarks were assigned to both left and right forewing. Data were appended and file were linked in tps util and the ordination of the shapes' consensus was illustrated and consensus shape data (mean shape) of the populations was measured by a relative warp ordinations plot using tpsRelw 1.36. Relative warp scores were then subjected to Multivariate Analysis of Variance (MANOVA), Canonical Variate Analysis (CVA) and Kruskal Wallis test using PAST software version 2.0. Visualization of variations was done using histograms and boxplots. Results showed significant morphological variation in the forewings.